Land System Reform in Rural China: Path and Mechanism - Shi, Xinjie; Gao, Xuwen; Fang, Shile (Land (Basel), 2022)
Changes in land policy not only determine agricultural growth, but also have bearing on issues, such as peasants’ rights and interests, industrial development, and urbanization. On account of China’s singular history and culture, its land systems are somewhat unique. This paper analyzes the institutional changes that took place before and after 1978 to show the journey of land system reform in rural China in the 20th century. We look closely at the policy performance and drawbacks of the reform that occurred after 1978, and analyze a series of “Central First Documents” that concern rural issues. Based on this analysis, some prospective land policy reforms are predicated. We conclude that at present, rural land ownership is unlikely to be completely privatized in the short-term. Creating a new agricultural management system with special functions or a land shareholding system, could be suitable measures to overcome the disorder of the existing land policy system in China.